PENGARUH CURRENT RATIO, TOTAL ASSETS TURNOVER, DAN RETURN ON INVESTMENT TERHADAP KINERJA PERUSAHAAN PADA INDUSTRI FOOD AND BEVERAGES YANG TERDAFTAR DI BEJ - Srimindarti, Ceacilia (Jurnal Ilmiah Telaah Manajemen, 2009)
This study aimto analyze the influence of current ratio, total assets turnover, and return on investment to performance on food and beverage company that listed in Jakarta Stock Exchange. The population in this study were food and beverage company that listed in Jakarta Stock Exchange. Sampling method were used in this study was purposive sampling. Regression analysis were used to testing influence current ratio, return on investment, and total assets turnover to performance which proxied by earning after tax. The results of this study found that current ratio and total assets turnover have positive andsignificant impact on performance. On the other hand return on investment has no influence to performance.Key Words: current ratio, total assets turnover, return on investment, performance.